Synthesis and cytotoxic evaluation of some derivatives of triazole-quinazolinone hybrids - Farshid Hassanzadeh; Hojjat Sadeghi-aliabadi; Shadan Nikooei; Elham Jafari; Golnaz Vaseghi (Wolters Kluwer Medknow Publications, 2019)
Triazoles and quinazolinones are important heterocyclic structures with diverse biological properties including cytotoxic, antibacterial, antifungal and anticonvulsant activities. Due to valuable cytotoxic effects of both triazole and quinazoline derivatives, in this study a series of quinazolinone-triazole hybrids were synthesized in a multiple-step reaction procedure. 3-Amino-quinazolinone derivatives were treated with chloroacetyl chloride in the presence of dichloromethane/triethylamine to afford 2-chloro -N-(4-oxo-2- quinazolin3 (3H)-yl) acetamide derivatives. The reaction of resultants with 4-mehyl-4-H-1, 2, 4-triazole-3- thiol in dry acetone and potassium carbonate led to the formation of final products. Synthesized compounds were evaluated for their cytotoxic effects against MCF-7 and Hela cell lines using MTT colorimetric assay. Amongst tested compounds, 6a showed the highest cytotoxic activity against MCF7 cell line at all tested concentrations while compounds 6b and 6c indicated mild cytotoxic effects against Hela cell line at highest tested concentration reducing cell viability about 40%. The IC50 values of tested compounds revealed that the MCF-7 is more susceptible to the compound 6a.